2019
DOI: 10.3389/fpubh.2019.00236
|View full text |Cite
|
Sign up to set email alerts
|

Communication Needs for Individuals With Rare Diseases Within and Around the Healthcare System of Northern Ireland

Abstract: Objective: By definition a rare disease affects fewer than 1 in 2,000 people but collectively 1 in 17 people are affected at some time in their lives. Rare disease patients often describe feeling isolated and unsupported. The needs of individuals living with rare disease(s) are not well met globally and have not been specifically explored in Northern Ireland. Methods: An online survey was conducted in spring of 2017, focused on information and communication needs, to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 39 publications
6
44
0
Order By: Relevance
“…Accurate and timely diagnosis is essential for early recognition of rare genetic disease and management preventive life- long impairments, which means the newborn screening programme to be uniformly applied to across the European member states to offer equal quality of care and service for every child born in Europe 25 , 26 . (3) Education and training were identified as the third research priority, and this is consistent with recent studies 28 , 29 and highlighted the need for providing accessible education and training for families and the community. Those studies have reported the requisite for primary care physician’s knowledge and understanding of rare diseases and the need to create information sessions for professionals and students.…”
Section: Discussionsupporting
confidence: 78%
“…Accurate and timely diagnosis is essential for early recognition of rare genetic disease and management preventive life- long impairments, which means the newborn screening programme to be uniformly applied to across the European member states to offer equal quality of care and service for every child born in Europe 25 , 26 . (3) Education and training were identified as the third research priority, and this is consistent with recent studies 28 , 29 and highlighted the need for providing accessible education and training for families and the community. Those studies have reported the requisite for primary care physician’s knowledge and understanding of rare diseases and the need to create information sessions for professionals and students.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, there is a need for discussion on ensuring the data we generate is publicly available, whilst protecting patient confidentiality, to enable large scale collaborative efforts, a phenomenon which would be particularly helpful for diagnosing currently undiagnosed patients. Such a discussion and development of resources should involve continuous consultation with patients and their family members [16,153].…”
Section: Triglyceride Deposit Cardiomyovasculopathy Unknownmentioning
confidence: 99%
“…For example, a national survey of rare disease patients and carers in Northern Ireland showed that 63% of participants reported attending multiple doctors with 7% reporting management by greater than 10 doctors [14]. The nature of typical patient confidentiality can make essential communication between healthcare teams difficult, particularly with care across multiple centres and when accessing external specialist centres of excellence, thus leading to further delays in the diagnosis of a rare disease and fragmented patient care [4, 15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this lack of deep investigation of the social media interaction phenomenon for this complex rheumatic disease, patient associations, healthcare communities, blog pages, and patients are active on social media in order to seek information and increase awareness among the general public. In most cases, patients use these channels for emotional and peer health support [ 12 , 13 ], often searching for new treatments or healthcare decision suggestions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%